2021
DOI: 10.1177/15500594211062702
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of the Ictal Electrocorticographic Discharges Confined to the Medial Temporal Lobe to the Scalp-Recorded Electroencephalogram

Abstract: Objective: Previous reports on the simultaneous recording of electroencephalography (EEG) and electrocorticography (ECoG) have demonstrated that, in patients with temporal lobe epilepsy (TLE), ictal ECoG discharges with an amplitude as high as 1000 μV originating from the medial temporal lobe could not be recorded on EEG. In contrast, ictal EEG discharges were recorded after ictal ECoG discharges propagated to the lateral temporal lobe. Here, we report a case of TLE in which the ictal EEG discharges, correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In terms of the ictal discharges, the MA and CH electrodes also could detect ictal events from the hippocampal onset, the same as other extracranial electrodes. Our previous report[ 7 ] demonstrated that highly synchronized intracranial ictal discharges with high amplitudes >1500–2000 μV in the mesial temporal lobe could be recorded by the extracranial electrodes as ictal extracranial EEG discharges through volume conduction. It is considered that the sensitivity of ictal discharge detection of MA and CH electrodes is also comparable to other extracranial electrodes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of the ictal discharges, the MA and CH electrodes also could detect ictal events from the hippocampal onset, the same as other extracranial electrodes. Our previous report[ 7 ] demonstrated that highly synchronized intracranial ictal discharges with high amplitudes >1500–2000 μV in the mesial temporal lobe could be recorded by the extracranial electrodes as ictal extracranial EEG discharges through volume conduction. It is considered that the sensitivity of ictal discharge detection of MA and CH electrodes is also comparable to other extracranial electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…MTLE patients undergo epilepsy surgery without invasive examination in our institution and we rarely have the chance to perform simultaneous intra- and extracranial recordings. [ 7 ] Second, we examined the IEDs detected in extracranial EEG monitoring during 100 consecutive IEDs and only two ictal discharges. Hence, we could only discuss the sensitivity but not the specificity of MA and CH electrodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations